ANALYSIS OF ACQUIRE AND IMPLEMENT OF LIBRARY INFORMATION SYSTEM USING COBIT 4.1 FRAMEWORK - Magdalena, Hilyah (STMIK Royal, 2024)
Abstract: College libraries are built and designed based on the needs of the academic community to support learning, research, and community service. Management of higher education institutions in Indonesia refers to Organizing libraries in Indonesia is regulated in National Library Director Regulation No. 13 of 2017. College libraries currently use information technology to support operations. To assess the alignment of a university's goal of providing a library that complies with information technology regulations and management, library management needs to be audited. At the ISB Atma Luhur library, audits were carried out using the COBIT 4.1 framework. especially in the Acquire and Implement (AI) domain. The AI domain is a domain that assesses whether plans have been successfully acquired and implemented. This research uses interview and questionnaire methods as primary data source data collection media. The respondents involved were the head of the library and the ISB Atma Luhur library staff. The results of data processing show that the AI domain is at 2,754 with a maturity level of 3-Define Process. Of the 7 control objectives under the AI domain, AI4 Anable Operation and Use is the highest control objective with 3.28. Meanwhile, the lowest control objective is AI2 Acquire and maintain application software with 2.50. Keywords: acquire and implement COBIT 4.1; college library ; information systems audit. Abstrak: Perpustakaan perguruan tinggi dibangun dan dirancang berdasarkan kebutuhan civitas akademika untuk menunjang pembelajaran, penelitian dan pengabdian kepada masyarakat. Pengelolaan perguruan tinggi di Indonesia mengacu pada Penyelenggaraan perpustakaan di Indonesia diatur dalam Peraturan Kepala Perpustakaan Nasional Nomor 13 Tahun 2017. Perpustakaan perguruan tinggi saat ini sudah memanfaatkan teknologi informasi untuk menunjang operasionalnya. Untuk menilai keselarasan tujuan perguruan tinggi dalam menyediakan perpustakaan yang sesuai dengan regulasi dan pengelolaan teknologi informasi, maka pengelolaan perpustakaan perlu dilakukan audit. Pada perpustakaan ISB Atma Luhur, audit dilakukan dengan menggunakan framework COBIT 4.1. khususnya di domain Acquire and Implement (AI). Domain AI adalah domain yang menilai apakah rencana telah berhasil diperoleh dan diterapkan. Audit sistem informasi perpustakaan ini bertujuan untuk menilai keselarasan rencana dan akuisisi impelentasi sistem untuk meningkatkan layanan perpustakaan. Penelitian ini menggunakan metode wawancara dan angket sebagai media pengumpulan data sumber data primer. Responden yang terlibat adalah kepala perpustakaan dan staf perpustakaan ISB Atma Luhur. Hasil pengolahan data menunjukkan domain AI berada pada angka 2.754 dengan tingkat kematangan 3-Define Process. Dari 7 tujuan pengendalian dalam domain AI, AI4 Anable Operation and Use merupakan tujuan pengendalian tertinggi dengan nilai 3,28. Sedangkan tujuan pengendalian terendah adalah AI2 Memperoleh dan memelihara perangkat lunak aplikasi dengan nilai 2,50. Kata kunci: acquire and implement COBIT 4.1.; audit sistem informasi; perpustakaan perguruan tinggi.